Analisis rasio keuangan untuk menilai kinerja keuangan pada PT Unilever Indonesia Tbk Tahun 2022-2023 - Diah Sohnya Pratika; Dewi Anggraini Kusuma Wardani; Enrico Firzatullah Maulana; M. Thoha Ainun Najib (Jurnal Mutiara Ilmu Akuntansi, 2024)
Financial performance of PT. Unilever Indonesia Tbk is evaluated using financial statement analysis. The purpose of this study is to evaluate the financial performance of PT. Unilever Indonesia Tbk from 2022 to 2023 through financial statement analysis. The time series analysis method is used to understand changes in a company’s financial performance over time. It involves the use of various financial ratios including liquidity, solvency, activity, and profitability ratios. This research uses a quantitative descriptive approach, which means that the data collected is quantitative data from the annual financial statements of PT. Unilever Indonesia Tbk (secondary data) for 2022 and 2023. The analysis results show the company’s liquidity ratio is below industry standards, indicating challenges in paying off short-term obligations. Although the cash ratio will increase in 2023, the value is still not ideal. In terms of solvency, the ratio of debt to asset and debt to equity indicates a high dependence on debt. However, the company performed well in profitability, with profit margins, return on assets (ROA), and return on equity (ROE) above the industry average, reflecting effectiveness in generating profits and managing assets and capital. The inventory turnover ratio is below industry standard, but total asset turnover shows good performance, indicating effective asset management to generate sales.